Infotainment in the campaign for the 2015 Spanish general election: An analysis of El Hormiguero from a gender perspective - Rodríguez Pérez, María Pilar; Berasategi, Miren (Cuestiones de Género: de la igualdad y la diferencia, 2016)
Within the new landscape of political communications characterized by infotainment in prime time television programs, this article analyzes the presence of four political representatives in El Hormiguero to explore if their appearances reinforce gender stereotypes. The analysis of the television programs reveals a substantial progress in the elimination of gender stereotypes which the media traditionally convey and reproduce in political campaigns. The analysis reveals a practical elimination of gendered bias in the interviews; the sexist tone remains, however, in other spaces of the television program linked to humor and entertainment practices.